UPAYA PENINGKATAN KINERJA SEKSI PENGENDALIAN DAN PEMBERANTASAN PENYAKIT MENULAR (PENYAKIT TUBERKULOSIS) DALAM PENANGGULANGAN KASUS DI KABUPATEN MAGELANG - Anastasia Erni Budi Kristiani; Priyastiwi Priyastiwi (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2021)
This Research aims to know the efforts of performance-improvement officer of tuberculosis in Kabapaten. Research conducted in January to Pebruary 2019. This type of research is descriptive research using qualitative data collection with interviews and observations as well as a questionnaire distributed in the respondents in this case in the relevant manner in later interviews So the conclusion to be pulled. The results showed that the performance of the program of tuberculosis in Maas Regency of clinics continues to be low it was proven by the low level of commitment of local policy pemixing ku and less cross-sector cooperation in each region and However, the entire Tatalaksana programme financed in accordance with the procedures. Therefore, recommend local policy makerst The UNITED Kingdom can build devotion in the tuberculosis program activities with all partyoR at each area and the implementation of the Programme in accordance with the Tuberculosis prevention Tatalaksana.